2019
DOI: 10.17996/anc.19-00090
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Risk Stratification of Cardiac Events Evaluated by Aortic Calcification in Elderly Patients with Chronic Kidney Disease

Abstract: Background: The relationship between myocardial perfusion imaging (MPI) and aortic calcification (AoC) in chronic kidney disease (CKD) patients remains unclear. Methods: The Japanese Assessment of Cardiac Events and Survival Study by quantitative gated single-photonemission computed tomography (J-ACCESS 3) is a multicenter, prospective cohort study investigating the ability of MPI to predict cardiac events in 529 CKD patients. In J-ACCESS 3, the sum of myocardial perfusion defect score at stress (SSS) was a us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The present study aimed to compare differences in (15). In addition, subanalysis of the J-ACCESS database revealed a relationship between major cardiac events and perfusion SPECT findings in patients with CKD (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study aimed to compare differences in (15). In addition, subanalysis of the J-ACCESS database revealed a relationship between major cardiac events and perfusion SPECT findings in patients with CKD (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Although this J-ACCESS subanalysis demonstrated that SPECT had incremental value for predicting cardiac events (18,19), the study population did not include patients with endstage renal disease requiring hemodialysis and was similar to our population of patients with mild CKD. On the other hand, several studies have reported that stress myocardial perfusion SPECT is useful for detecting ischemic heart disease and predicting cardiac events in hemodialysis patients (16,20,21); the population of those studies was similar to our population of patients with severe CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5, p 35(16); if "B blocker (%)" represents our treatment of interest and Aortic cal + /-our variable of interest, which provides two proportions for the B blocker and the control groups for comparison, we would set 1. Zα/2=1.…”
mentioning
confidence: 99%